Simultaneous synthesis and consolidation of a nanocrystalline 8.33Fe(0.24)Cr(0.43)Al(0.25)Si(0.08)-Al2O3 composite by high-frequency induction heating - Shon, In-Jin; Du, Song-Lee; Ko, In-Yong; Doh, Jung-Mann; Yoon, Jin-Kook; Park, Sang-Whan (KOREAN ASSOC CRYSTAL GROWTH, INC, 2011)
Nanopowders of Fe2O3, Cr, Si, and Al powders were fabricated by high-energy ball milling. A high-density nanocrystalline 8.33Fe(0.24)Cr(0.43)Al(0.25)Si(0.08) -Al2O3 composite was simultaneously synthesized and consolidated by a high-frequency, induction-heated sintering (HFIHS) method within two minutes from mechanically activated powders of Fe2O3, Cr, Si, and Al. The advantage of this process is that it allows very quick densification to near theoretical density and prohibits grain growth in nano-structured materials. The hardness of the composite was about 1060 kg/mm(2).
Keywords: POWDERS; ALLOY; METALS; WC